Systematic discovery and characterization of fly microRNAs using 12 Drosophila genomes - Stark, Alexander; Kheradpour, Pouya; Parts, Leopold; Brennecke, Julius; Hodges, Emily; Hannon, Gregory J.; Kellis, Manolis (Genome Research, 2007)
MicroRNAs (miRNAs) are short regulatory RNAs that inhibit target genes by complementary binding in 3′ untranslated regions (3′ UTRs). They are one of the most abundant classes of regulators, targeting a large fraction of all genes, making their comprehensive study a requirement for understanding regulation and development. Here we use 12 Drosophila genomes to define structural and evolutionary signatures of miRNA hairpins, which we use for their de novo discovery. We predict >41 novel miRNA genes, which encompass many unique families, and 28 of which are validated experimentally. We also define signals for the precise start position of mature miRNAs, which suggest corrections of previously known miRNAs, often leading to drastic changes in their predicted target spectrum. We show that miRNA discovery power scales with the number and divergence of species compared, suggesting that such approaches can be successful in human as dozens of mammalian genomes become available. Interestingly, for some miRNAs sense and anti-sense hairpins score highly and mature miRNAs from both strands can indeed be found in vivo. Similarly, miRNAs with weak 5′ end predictions show increased in vivo processing of multiple alternate 5′ ends and have fewer predicted targets. Lastly, we show that several miRNA star sequences score highly and are likely functional. For mir-10 in particular, both arms show abundant processing, and both show highly conserved target sites in Hox genes, suggesting a possible cooperation of the two arms, and their role as a master Hox regulator.